Systematic Review on the Incidence of Bisphosphonate Related Osteonecrosis of the Jaw in Children Diagnosed with Osteogenesis Imperfecta - Anusha Adeline Hennedige; Jap Jayasinghe; Janette Khajeh; Tatiana V. Macfarlane (Stilus Optimus, 2014)
Objectives: To conduct a systematic review of epidemiological literature to determine the incidence of bisphosphonate related osteonecrosis of the jaw occurring either spontaneously or after dental surgery, in children and adolescents diagnosed with osteogenesis imperfecta. Material and Methods: MEDLINE, HMIC and EMBASE were used to search for English-language articles published from 1946 - 2013. Inclusion criteria consisted of population based studies of children and adolescents (24 years and younger) diagnosed with osteogenesis imperfecta, only studies which included a dental examination, and patients treated with intravenous bisphosphonates were included. Articles were excluded if patients had any other co-morbidity which could affect osteonecrosis of the jaw, and those which treated patients with oral bisphosphonates only. Results: Five studies consisting of four retrospective cohort studies and one case series were identified. Study populations ranged from 15 to 278 patients and number of subjects with osteogenesis imperfecta ranged from 15 to 221. Mean duration of intravenous bisphosphonate use ranged from 4.5 to 6.8 years. All patients were clinically examined and no patients were found to have osteonecrosis of the jaw. Conclusions: There is no evidence to support hypothesis of causal relationship between bisphosphonates and osteonecrosis of the jaw in children and adolescents with osteogenesis imperfecta. More prospective studies on bisphosphonate use in osteogenesis imperfecta needs to be carried out.